2019
DOI: 10.15171/joddd.2019.017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of length, diameter and position of the implant in its fracture incidence: A Systematic Review

Abstract: Background. Implant fractures can cause difficult problems for patients and dentists. This systematic review aimed to determine the influence of some implant parameters on the occurrence of their fracture and to determine the incidence of fractures reported in recent years. Methods. A search was conducted in Pubmed database, from which 12 studies published in the last 12 years were selected. Results. This review reported a 2% incidence of implant fracture. Most implants had been in function between 3 and 4 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
(65 reference statements)
0
2
0
1
Order By: Relevance
“…In our opinion, this can also be seen as an advantage since it probably indicates that IP is unlikely to affect the fracture resistance in more favorable scenarios where regular- or large-platform implants are involved. Also, splinted restorations supported by several narrow implants are likely to have a better mechanical behavior and therefore less risk of fracture ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, this can also be seen as an advantage since it probably indicates that IP is unlikely to affect the fracture resistance in more favorable scenarios where regular- or large-platform implants are involved. Also, splinted restorations supported by several narrow implants are likely to have a better mechanical behavior and therefore less risk of fracture ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…This review adopted the classification of implant diameter as proposed by Al-Johany et al (2017), which described narrow platform diameter as ≥3.0 mm to <3.75 mm; regular diameter as ≥3.75 mm to <5 mm; and wide diameter as ≥5 mm. A recent systematic review that looked at dental implant fracture reported that implants of narrower diameter have a higher incidence of fracture (Goiato et al, 2019). Similarly, narrower implants in this systematic review were found to be at a higher risk of fracture after implantoplasty, especially in the presence of significant bone loss around the implant.…”
Section: Discussionmentioning
confidence: 51%
“…Casos donde la disponibilidad ósea en sentido horizontal sea menor a 6 mm o exista un espacio mesio-distal reducido, muy frecuente en el sector antero-inferior, la colocación de un implante de menor diámetro puede ser una buena alternativa. (1,2) Cada sistema de implantes tiene sus propios diámetros y longitudes que no coinciden necesariamente con otros sistemas. Además, no existe un acuerdo entre los fabricantes en términos de definición y categorización, portanto,no se dispone de un consenso internacional sobre la definición de lo que es un implante estrecho; no obstante, Quek et al (3) publicaron una clasificación que intentaba solucionar este problema.…”
Section: Introductionunclassified